THERMAL ANALYSIS AND TEMPERATURE DISTRIBUTION IN EARTH PIPE AIR HEAT EXCHANGER - Nofrizalidris Darlis; Muhammad Noor Afiq Witri Muhammad Yazid; Kumaran Kalimuthu; Aminuddin Saat; Fazila Mohd Zawawi; Asral (Applications of Computational Fluid Dynamics in Mechanical Engineering (Series 4), 2025)
Temperature of air that flows into underground tunnel can be cooled down, which can be utilized for reducing the cooling load of buildings. The present chapter aims to analyse the outlet air temperature of an earth pipe air heat exchanger (EPAHE) system. A transient and implicit model based on computational fluid dynamics was developed to predict the thermal performance of the EPAHE. Computational fluid dynamics (CFD) simulation is employed to determine the temperature distribution across the EPAHE system for different types of soil and with different range of air velocities. The transient study of temperature profile, velocity profile of the piping model has been conducted by using Renormalized Group (RNG) k−ε turbulent model. Effects of the operating parameters such as the type of soil and air velocity on the thermal performance of EPAHE systems are discussed. The 23.42 m long and 2.75 m depth inside the soil of EPAHE system discussed in this paper gives cooling in the range of 10.0 to 13.0℃ for the flow velocities 1 to 5 m/s in four different types of soils. We found the type of soil buried, and the flow of air velocity contributed to the major effect of the performance of EPAHE system. Keywords: earth pipe air heat exchanger, CFD, thermal analysis